2001
DOI: 10.1046/j.1365-2648.2001.01807.x
|View full text |Cite
|
Sign up to set email alerts
|

Communication skills of nurses during interactions with simulated cancer patients

Abstract: ( 2 0 0 1 ) ( 2 0 0 1 ) Journal of Advanced Nursing 34(6), 772±779 Communication skills of nurses during interactions with simulated cancer patients Aim. 2In this paper the balance of affective and instrumental communication employed by nurses during the admission interview with recently diagnosed cancer patients was investigated. Rationale. The balance of affective and instrumental communication employed by nurses appears to be important, especially during the admission interview with cancer patients. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0
4

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 25 publications
3
70
0
4
Order By: Relevance
“…Nurses should provide some effort to overcome these barriers. [1,6] On the other hand, preparation of specific health messages should elicit the desired patient behavior as well as grasp their attention. Health communication messages need to be focused on real concerns and not diluted with extraneous data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nurses should provide some effort to overcome these barriers. [1,6] On the other hand, preparation of specific health messages should elicit the desired patient behavior as well as grasp their attention. Health communication messages need to be focused on real concerns and not diluted with extraneous data.…”
Section: Discussionmentioning
confidence: 99%
“…Four questions were added to explore the problems that nurses encountered in health communication from patients' perspectives according to a review of related literature. [1,6,15] Then the tool was submitted to a jury of seven experts in nursing education, medical surgical nursing and health education fields to ensure tool content validity. Reliability was measured using the Cronbach Alpha Reliability Test with values ranging from 0.66 to 0.72.…”
Section: Study Toolmentioning
confidence: 99%
See 1 more Smart Citation
“…Communication issues also impact upon patients' families: Davis et al (2003) found that after pain management, poor communication with health professionals created the most distress for the families of cancer patients. Kruijver et al (2001) found that when ward nurses interacted with cancer patients they predominately employed instrumental communication, mostly consisting of giving information about medical topics. There was an imbalance in favour of instrumental communication at the expense of affective communication.…”
Section: Needs Of Health Care Professionals In Delivering Carementioning
confidence: 99%
“…Whilst some studies indicate that communication skills can improve through education and training (Maguire et al, 1996;Razavi et al, 2000;Wilkinson et al, 2002), other studies suggest that the skills obtained from communication courses have not been applied within the clinical setting (Kruijver et al, 2000(Kruijver et al, , 2001. Nonetheless, the drive to improve the patient assessment using a standardised approach by all health professionals has placed assessment of patients' needs (and communication skills) as central to the whole process of providing quality cancer care (NICE, 2004;National Audit Office, 2005).…”
Section: A U T H O R ' S P E R S O N a L C O P Ymentioning
confidence: 99%